Implementation of Inter-Building Wireless Backhaul using Ubiquiti 5AC Gen2 and MikroTik - Hashfi Adha Fadhillah; Ichwan Nul Ichsan (Universitas Islam Indragiri, 2026)
This study aims to implement and evaluate the performance of an inter-building wireless backhaul network using the Ubiquiti LiteBeam 5AC Gen2 integrated with a MikroTik router as a solution for internet distribution without the need to subscribe to an additional ISP service. The study is motivated by the increasing demand for high-speed and reliable network connectivity between buildings, while wired network implementations are often limited in terms of cost and installation flexibility. The research adopts an experimental approach with descriptive quantitative analysis through direct measurement of Quality of Service (QoS) parameters, including throughput, delay, and jitter. Testing was conducted under three scenarios: a direct wireless backhaul link, a WiFi network on the first floor, and a WiFi network on the second floor of the building. The results show that the wireless backhaul provides an average throughput of 87.95 Mbps for download and 48.60 Mbps for upload, with a delay of 1.19 ms. On the access network side, the achieved throughput remains sufficient for user needs, although delay and jitter increase as the number of connected devices and traffic load grows. This study concludes that the implementation of an IEEE 802.11ac-based wireless backhaul using Ubiquiti LiteBeam 5AC Gen2 and MikroTik is effective as a medium-scale inter-building connectivity solution, delivering performance that meets typical daily internet service requirements.